Local governance of disasters risk in metropolitan areas. case of the Nonguén valley, Concepción, Chile - Burdiles, Roberto (2023)
Concepción is the second most relevant metropolitan area in Chile. Inside the Nonguén National Park, located in this area, are various human settlements, near the watercourse that cross the valley. Local-scale disasters are a concern for these communities. Due to the climate change, Nonguen´s biodiversity is threatened by floods, mass removal and forest fires. The latter have had an important increment in the last years. In this research, an interpretation of the reach of local governance of disasters risk from the perspective of local leaders of Nonguén is carried out. To that effect, 18 community leaders answered semi- structured interviews. The results describe the perceptions of the community about disaster and the spatial conditions for local governance, specially towards climate change. The conclusion is that participation and empowerment of communities are key elements to promote a type of local governance that considers the risks of climate change. Finally, this is a political and technical issue that tends to project in recurring and problematic ways in metropolitan areas in developing countries.